Qoraqalpogʻistonda yantoq (Alhagi) dorivor oʻsimligi zararkunandalari (SCIENCE and SOCIETY, 2025)
The article provides information on the species composition of the pests of the alhagi medicinal plant, which grows naturally in the Republic of Karakalpakstan.